Colours Obtained from Safflower (Carthamus tinctorius L.) Types and Their Fastness Values - Kayabasi, N.; Basalma, D.; Sanli, H.S. (Asian Journal of Chemistry, 2012)
Safflower is planted on small fields in the world among single year oily flowering plants. Today, nearly 50 % of the vegetable oils consumed in Turkey is imported. Safflower, being an alternative oil plant, can be raised easily in arid regions. This plant has resistance against cold, drought and salinity stress. In this study, when C1 = Yenice (spineless, orange coloured), C2 = Dinçer (spineless, red coloured) and C3 = Remzibey-05 (spined, yellow coloured) safflower types are used in dyeing, the determination of light and abrasion fastness values are aimed.